Relationship skills in social work - Hennessey, R. A. S. [ (Roger A. S.)] (SAGE, 2011)
Human relationships lie at the heart of social work practice, and an understanding of their importance is a crucial aspect of training. This text considers the place of relationships in current practice and explores the ways in which social workers can use relationship skills to achieve the best possible outcomes for their clients.